Evaluation of the genotoxic potential of acrylamide: Arguments for the derivation of a tolerable daily intake (TDI value) - Sabine Guth; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Dirk Haller; Volker Heinz; Michael Hellwig; Jan G. Hengstler; et al. (Food and Chemical Toxicology, 2023)

Stellungnahme zu Acetaldehyd als Aromastoff: Aspekte der Risikobewertung - Jan G. Hengstler; Matthias Baum; Alexander T. Cartus; Patrick Diel; Gerhard Eisenbrand; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; et al. (Journal of Consumer Protection and Food Safety, 2022)
Opinion on acetaldehyde as a flavouring substance: considerations for risk assessment Acetaldehyde occurs naturally in many foods and is also used as a flavouring due to its fruity aroma. The International Agency for Research on Cancer (IARC) classified acetaldehyde as possibly carcinogenic to humans and, in combination with oral intake via alcoholic beverages, as carcinogenic to humans. Therefore, the question arises whether the use of acetaldehyde as a flavouring agent is still justifiable. The Senate Commission on Food Safety (SKLM) of the German Research Foundation (DFG) reviewed the scientific basis for health risk assessment of the use of acetaldehyde as a flavouring substance and adopted an opinion. Based on the available data, it is at present not possible to conclude if acetaldehyde is genotoxic and mutagenic in vivo after oral exposure. There is also uncertainty regarding the contribution of acetaldehyde as a flavouring substance to the overall exposure to acetaldehyde. Therefore, a science-based assessment on health risk related to the use of acetaldehyde as a flavouring is not possible at present. Considering the genotoxic potential as well as numerous data gaps that need to be closed for a full risk assessment, the SKLM is concerned about the safety of acetaldehyde as a flavouring substance. For reasons of precautionary consumer protection, the SKLM considers that the use of acetaldehyde as a food additive should be re-evaluated.

Salivary nitrate/nitrite and acetaldehyde in humans: potential combination effects in the upper gastrointestinal tract and possible consequences for the in vivo formation of N-nitroso compounds—a hypothesis - Gerhard Eisenbrand; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; Michael Hellwig; et al. (Archives of Toxicology, 2022)

Contribution to the ongoing discussion on fluoride toxicity - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2021)
Since the addition of fluoride to drinking water in the 1940s, there have been frequent and sometimes heated discussions regarding its benefits and risks. In a recently published review, we addressed the question if current exposure levels in Europe represent a risk to human health. This review was discussed in an editorial asking why we did not calculate benchmark doses (BMD) of fluoride neurotoxicity for humans. Here, we address the question, why it is problematic to calculate BMDs based on the currently available data. Briefly, the conclusions of the available studies are not homogeneous, reporting negative as well as positive results; moreover, the positive studies lack control of confounding factors such as the influence of well-known neurotoxicants. We also discuss the limitations of several further epidemiological studies that did not meet the inclusion criteria of our review. Finally, it is important to not only focus on epidemiological studies. Rather, risk analysis should consider all available data, including epidemiological, animal, as well as in vitro studies. Despite remaining uncertainties, the totality of evidence does not support the notion that fluoride should be considered a human developmental neurotoxicant at current exposure levels in European countries.

Toxicity of fluoride: critical evaluation of evidence for human developmental neurotoxicity in epidemiological studies, animal experiments and in vitro analyses - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2020)
Recently, epidemiological studies have suggested that fluoride is a human developmental neurotoxicant that reduces measures of intelligence in children, placing it into the same category as toxic metals (lead, methylmercury, arsenic) and polychlorinated biphenyls. If true, this assessment would be highly relevant considering the widespread fluoridation of drinking water and the worldwide use of fluoride in oral hygiene products such as toothpaste. To gain a deeper understanding of these assertions, we reviewed the levels of human exposure, as well as results from animal experiments, particularly focusing on developmental toxicity, and the molecular mechanisms by which fluoride can cause adverse effects. Moreover, in vitro studies investigating fluoride in neuronal cells and precursor/stem cells were analyzed, and 23 epidemiological studies published since 2012 were considered. The results show that the margin of exposure (MoE) between no observed adverse effect levels (NOAELs) in animal studies and the current adequate intake (AI) of fluoride (50 µg/kg b.w./day) in humans ranges between 50 and 210, depending on the specific animal experiment used as reference. Even for unusually high fluoride exposure levels, an MoE of at least ten was obtained. Furthermore, concentrations of fluoride in human plasma are much lower than fluoride concentrations, causing effects in cell cultures. In contrast, 21 of 23 recent epidemiological studies report an association between high fluoride exposure and reduced intelligence. The discrepancy between experimental and epidemiological evidence may be reconciled with deficiencies inherent in most of these epidemiological studies on a putative association between fluoride and intelligence, especially with respect to adequate consideration of potential confounding factors, e.g., socioeconomic status, residence, breast feeding, low birth weight, maternal intelligence, and exposure to other neurotoxic chemicals. In conclusion, based on the totality of currently available scientific evidence, the present review does not support the presumption that fluoride should be assessed as a human developmental neurotoxicant at the current exposure levels in Europe.

Physical properties and microstructures of La $$_{1-{x}}$$ 1 - x Pr $$_{{x}}$$ x PO $$_4$$ 4 monazite-ceramics - Anja Thust; Antje Hirsch; Eiken Haussühl; Nadine Schrodt; Lise Loison; Petra Schott; Lars Peters; Georg Roth; Björn Winkler (Physics and Chemistry of Minerals, 2018)

A neutron diffraction study of crystal and low-temperature magnetic structures within the (Na,Li)FeGe2O6 pyroxene-type solid solution series - Günther J. Redhammer; Anatoliy Senyshyn; Stefan Lebernegg; Gerold Tippelt; Edgar Dachs; Georg Roth (Physics and Chemistry of Minerals, 2017)

Phytoremediation using microbially mediated metal accumulation in Sorghum bicolor - René Phieler; Dirk Merten; Martin Roth; Georg Büchel; Erika Kothe (Environmental Science and Pollution Research, 2015)

Der Hydro-Fischlift: Eine innovative Lösung für den Fischaufstieg — Aspekte zu Konstruktion und Betrieb - Andreas Roth; Georg Baumann (WASSERWIRTSCHAFT, 2015)

Structural and magnetic phase transitions in the synthetic clinopyroxene LiCrGe2O6: a neutron diffraction study between 0.5 and 1473 K - Günther J. Redhammer; Anatoliy Senyshyn; Gerold Tippelt; Sebastian Prinz; Georg Roth (Physics and Chemistry of Minerals, 2015)

Neue Aspekte der Regulation von Zelltod in Tumoren - Georg Gdynia; Wilfried Roth (BIOspektrum, 2011)

Nuclear and incommensurate magnetic structure of NaFeGe2O6 between 5 K and 298 K and new data on multiferroic NaFeSi2O6 - Günther J. Redhammer; Anatoliy Senyshyn; Martin Meven; Georg Roth; Sebastian Prinz; Astrid Pachler; Gerold Tippelt; Clemens Pietzonka; Werner Treutmann; Markus Hoelzel; Björn Pedersen; Georg Amthauer (Physics and Chemistry of Minerals, 2011)

Thermal expansion and high-temperature P21/c–C2/c phase transition in clinopyroxene-type LiFeGe2O6 and comparison to NaFe(Si,Ge)2O6 - Günther J. Redhammer; Fernando Cámara; Matteo Alvaro; Fabrizio Nestola; Gerold Tippelt; Sebastian Prinz; Jan Simons; Georg Roth; Georg Amthauer (Physics and Chemistry of Minerals, 2010)

Magnetic and nuclear structure and thermal expansion of orthorhombic and monoclinic polymorphs of CoGeO3 pyroxene - Günther Josef Redhammer; Anatoliy Senyshyn; Gerold Tippelt; Clemens Pietzonka; Georg Roth; Georg Amthauer (Physics and Chemistry of Minerals, 2010)

BLOC1S2 interacts with the HIPPI protein and sensitizes NCH89 glioblastoma cells to apoptosis - Georg Gdynia; Judith Lehmann-Koch; Sebastian Sieber; Katrin E. Tagscherer; Anne Fassl; Hanswalter Zentgraf; Shu-Ichi Matsuzawa; John C. Reed; Wilfried Roth (Apoptosis, 2008)

Concentration-dependent stimulatory and inhibitory effect of troglitazone on insulin-induced fatty acid synthase expression and protein kinase B activity in 3T3-L1 adipocytes - Andreas Barthel; Klaus-Dieter Krüger; Richard Roth; Hans-Georg Joost (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

ber antibiotische Wirkungen von drei Pseudomonasarten auf Wachstum und Mycelbildung von samenbegleitenden Pilzen sowie Bacillus cereus var. mycoides - Georg Roth (Archives of Microbiology, 1959)